سؤال الهوية و الهامش او الاغتراب المضاعف في رواية "كاماراد"- رفيق الحيف والضياع- للزيواني - بوراس, عبد الخالق (University of El-oued, 2020)
رواية" كاماراد" رفيق الحيف والضياع من الروايات القليلة التي خاضت موضوعا جديدا عن انواع السرد في الادب الجزائري، التي تبحث في سؤال الهوية وتعددها خارج اطار الثورة والحب والقضايا التي الفها القارئ في جل الروايات أنها تبحث في سؤال الهوية وتعددها، رحلة بحث عن الذات رحلة الى افاق تصبح فيه الهوية ضائعة فهي موقع رفض وقبول، مركز وهامش، فهي منجز نهائي منغلق عن ذاته وادراكها يتحقق بالتمازج والتداخل بين الذات والاخر، وهذا ما يؤدي الى تناقضات تتجسد في صورة اغتراب هذا الاخير ليس بالمفهوم المتعارف عليه في الدراسات النقدية والادبية، وانما انسلاخ الذات اجباريا عن هويتها الدينية لأجل مبتغى معينا يرى من خلاله تحقيق الامنيات الخيالية التي تراءت من الاوهام ،هذا ما أردنا معالجته في هذا المقال الذي يبحث في الظروف والملابسات التي ادت بهؤلاء الأفارقة الى الهجرة غير الشرعية وبطريقة غير قانونية التي انعكست على هوياتهم التي عاشت بين تيه الصحراء الكبرى بكل ماسيها وصعوباتها وانسلاخ هواياتهم واغتراب مضاعف. The novel "Kamarad" companion of injustice and loss of the few novels that fought a new topic on the types of narrative in Algerian literature, which examines the question of identity and its pluralism outside the framework of the revolution, love and issues that the reader has written in most novels that they are looking at the question of identity and plurality, a journey of self-search trip To the horizons where identity becomes lost it is a site of rejection and acceptance, center and margin, it is a final achievement closed from itself and its realization is achieved by mixing and overlapping between the self and the other, and this leads to contradictions embodied in the image of the alienation of the latter is not the concept accepted in the critical and literary studies, but dissolution Self-chore This is what we wanted to address in this article, which examines the circumstances and circumstances that led these Africans to illegal and illegal immigration, which was reflected on their identities that lived between the desert labyrinth. The grand with all its tragedies and difficulties and the dissolution of their hobbies and the alienation doubly.
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج03. ع.01. جامعة الوادي
Keywords: الهوية ،الاغتراب، الهجرة ،البحث عن الذات; identity, alienation, immigration, self-search